Utilization of WhatsApp for sharing livestock related information: An Experimental Study - Thakur, Devesh; Chander , Mahesh (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The paper is based on the use of WhatsApp in sharing of livestock related information among the farmers. A WhatsApp group of randomly selected 96 farmers from eight different districts of the Himachal Pradesh, India was created under the study. In a period of six months, information was shared in multiple forms among the farmers. A total of 62 queries during six months to seek information and advice on various livestock related problems were posted by the farmers. Maximum number of queries pertained to animal health followed by animal breeding, feeding, government programmes and dairy processing .The livestock extension agencies have the opportunity to explore and develop relevant information which can be disseminated through WhatsApp to the farmers.
Keywords: WhatsApp; Livestock extension; Queries